PERENCANAAN ULANG SISTEM DRAINASE UNTUK MENGATASI BANJIR PADA PEMUKIMAN PADAT PENDUDUK - Junelfan Daud; Arris Maulana; Anisah Anisah (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2019)
This study aims to overcome the floods that occur in densely populated areas by re-planning existingchannel dimensions. This research was conducted in the RW04 area, Cakung Barat Village, Cakung District,East Jakarta. This region has an area of 25.4ha with flat topography (5-6masl) and densely demographicconditions.The research method uses Quantitative Descriptive Methods. Data collection techniques used are byfield observation and analysis of rainfall data.The results obtained in the form of flood discharge, channel capacity, and plan channel dimensions.Re-planning is carried out on 7 channels that cannot withstand flood discharge by widening the cross section ofthe channel.